Transforming Household Waste Into Economic Opportunities: A Community-Based Empowerment Program In Rural Villages - Gunawan, Muhammad Indra Adi; Rahman, Abdur; Sintha, Farida; Septianingrum, Ika; Firman, Andi (PUDAK: Local Wisdom Community Journal, 2024)
Independent waste management in Sidomulyo Village, Mantup District, Lamongan Regency is a local government initiative to reduce the increasing volume of household waste. This program emphasizes active community participation through a waste bank, where each household is encouraged to sort waste at its source. Recyclable waste is collected, sold to collectors, and the proceeds are recorded as community savings. This mechanism not only contributes to environmental cleanliness but also creates economic opportunities for residents. The purpose of this study is to analyze the community empowerment process through independent waste management at the Sidomulyo Village waste bank. The research applied a descriptive qualitative method with data collected through interviews, observations, and documentation. Data analysis was carried out through data collection, reduction, presentation, and conclusion drawing. The findings indicate that community empowerment has been implemented quite effectively, as reflected in the residents’ involvement in waste sorting and savings management from the sale of recyclables. However, several challenges remain, particularly the limited support and facilitation from relevant institutions. Therefore, continuous evaluation and enhanced monitoring are required to optimize independent waste management and maximize its broader socio-economic impact.